Grandchildren's Depressive Symptoms and Perceptions of Family Functioning: Protective and Influencing Factors. (September 2018) - Musil, Carol M.; Rice, Heather M.; Singer, Mark; Givens, Sarah E.; Warner, Camille B.; Zauszniewski, Jaclene A.; Burant, Christopher J.; Toly, Valerie B.; Jeanblanc, Alexandra B.
A recent increase in children living with grandparents places more children at increased risk for emotional, psychological, or behavioral problems. This study used the Resiliency Model of Family Stress, Adjustment, and Adaptation to examine how children's living situation, parental monitoring, child's resourcefulness, and perceived support affect depressive symptoms and perceived family functioning. Of participants, 36% ( n = 56) lived with their parents only, 44% ( n = 69) lived with a grandmother as their primary caregiver, and 20% ( n = 31) lived in a multigenerational household. Results indicate parental monitoring and support affected perceptions of family functioning. Subjective support and resourcefulness affected depressive symptoms. No effects were found from living situation and demographic factors. Resourcefulness had the strongest effect on depressive symptoms, with a 3-point decrease in symptoms for each incremental increase in resourcefulness. This study provides insight into factors influencing children's depressive symptoms and perceived family functioning, and provides direction for the development of future interventions.